The quaternary evolutionary history of Bristol rock cress (Arabis scabra, Brassicaceae), a Mediterranean element with an outpost in the north-western Atlantic region - Koch, Marcus; Möbus, Johanna; Klöcker, Clara A.; Lippert, Stephanie; Ruppert, Laura; Kiefer, Christiane (Annals of botany, 2020)
AbstractBackground and Aims. Bristol rock cress is among the few plant species in the British Isles considered to have a Mediterranean-montane element. Spatiot
Electronically published: 24 March 2020
Gesehen am 18.09.2020